Manufactured goods' export diversification in Saudi Arabia: a spatial panel approach - Abdessalem Gouider; Hedi Ben Haddad (Cogent Economics & Finance, 2020)
This paper explores the potential spatial diversification of manufactured goods' exports in Saudi Arabia. To account for the spatial interactions of Saudi's manufactured goods' exports, we use a panel Spatial Autoregressive (SAR) model for 77 trade partners over the period 2000-2016. The empirical results suggest, firstly, the existence of spatial interdependence among Saudi's manufactured goods' exports. Secondly, we find that the exogenous variables including GDP, GDP per capita, trade freedom, bilateral exchange rate, and trade intensity index exert strong spillover effects on bilateral Saudi's manufactured goods' exports. Finally, the study demonstrates evidence of the highest potential with 34 out of 77 partners. This finding has important implications for policymakers, mainly in terms of development of the domestic manufacturing sector and geographic reallocation of Saudi's manufactured goods' exports.
Keywords: 330; panel Spatial autoregressive model; diversification; manufactured goods' exports; spillover effects; Saudi Arabia